Self-awareness of olfactory dysfunction in elderly individuals without neurodegenerative diseases - Toro, Mariana Dalbo Contrera; Demarco, Flávia Ribas; Giacomin, Lorena T.; da Cunha, Fernanda Rodrigues; dos Reis, Mariah G. Alves; Sakano, Eulália (European archives of oto-rhino-laryngology, 2023)
Purpose The decrease in smell in the elderly population is frequent and considered a natural process. However, sometimes it can be associated with the decline of cognitive functions, and it is considered a warning for the early stage of neurodegenerative diseases and social impairment. Objective To assess the prevalence of olfactory dysfunction in previous healthy elderly that attended a tertiary hospital in Brazil as escorts and the clinical alterations associated in this population. Methods Subjects 60 years or over attending the University Hospital of Campinas were evaluated. Each participant answered a questionnaire, followed by an otorhinolaryngological exam with flexible nasal endoscopy and the Connecticut smell test produced by the Connecticut Chemosensory Clinical Research Center (CCCRC). Elderly people with nasosinusal diseases or with a history of nasal surgery were excluded. Results Of the total of 103 participants, 16 (15.5%) reported olfactory complaints and 68 (66%) presented impairment in the olfactory test. It was observed that older individuals showed more changes in olfactory function ( p = 0.001). Gender, education, lifestyle, comorbidities, medications in use and exposure to pollutants did not influence the impairment olfactory function of this population. Conclusions There is a significant prevalence of olfactory dysfunction in the elderly population evaluated. Most of these elderlies also present an inability to identify odours, not having awareness of this olfactory impairment.